A framework to support multiple perspectives in eco-efficiency decisions - Farr, Richard; Arman, Hussam; Gindy, Nabil
Increasingly, it is recognised that human activity is causing our environment to degrade, and that there is a very real danger of doing irreversible damage to natural systems of which we have only a partial understanding. Neither living in, nor doing business in a future world with a degraded environment is desirable, and individuals and businesses alike are increasingly seeking ways to operate on a more sustainable basis.